Morfofunctional changes of the brain tissue after repeated mild brain injury (experimental research) - Nosov, A. T.; Kadjaya, N. V. (Ukrainian Neurosurgical Journal, 2006)
A repeated light head injury causes dystrophic-destructive changes in the brain structure, which are more marked than changes, caused by primary head injury These changes are characterized by extensive affection of microcirculation system in all brain sections being studied. As about microvessels, one month following a repeated head injury, endotheliocytes structure failure was observed, while capillary lumen expanded and erythrocytes statis and mural thrombosis occured. Changes in the cortex neurons in case of a repeated light head became stabilized only 60 days after the head injury, while changes in the synaptic system, although tending to restore, even 60 days after a repeated head injury were different from the control level. In case of a repeated head injury in all sections of the brain that were studied, and primarily in the area of the damaged hemisphere, gliosis prevailed and manifested itself in as increase of glial cells number mostly located in the areas of changed microvessels.